Gender Differences in Sorting - Luca Paolo Merlino; Pierpaolo Parrotta; Dario Pozzoli (Copenhagen Business School (CBS), Department of Economics, 2014)
In this paper, we investigate the sorting of workers in firms to understand gender gaps in labor market outcomes. Using Danish employer-employee matched data, we find strong evidence of glass ceilings in certain firms, especially after motherhood, preventing women from climbing the career ladder and causing the most productive female workers to seek better jobs in more female-friendly firms in which they can pursue small career advancements. Nonetheless, gender differences in promotion persist and are found to be similar in all firms when we focus on large career advancements. These results provide evidence of the sticky floor hypothesis, which, together with the costs associated with changing employer, generates persistent gender gaps.
hdl:10398/8929
Keywords: J16; J24; J62; 330; Sorting; Assortative Matching; Gender Gap; Glass Ceiling; Sticky Floor